Hemoblastosis. Acute Leukeosis - Karimova Shaxnoza Shavkatbek qizi; G’oyibnazarov Abdulla Abduaxat o’g’li; Abzalova Iroda Komoliddin qizi; Sayfutdinova Zuhra Abdurashid qizi (Genius Journals, 2024)
Hemoblastoses are tumors arising from hematopoietic cells. According to world statistics, leukemia is observed in 3.3-4.7 cases out of 100,000 children, children under 15 years of age. 40-46% of them correspond to children aged 2-6 years
Keywords: correspond; tumors; Hemoblastoses